The Influence Of Gender Diversity, Intellectual Capital, Inventory Turnover And Profitability On Financial Distress - Rahandri, Daniel; Surya Abbas, Dirvi; Magdalena, Crhista; Priadini, Dhesty; Silvia Anggraeni, Diva (BALANCE: Economic, Business, Management and Accounting Journal, 2025)
The purpose of this study was to determine the effect of gender diversity, intellectual capital, inventory turnover and profitability on financial distress in mining sector companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the period 2017 – 2021. The population of this study includes all mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. The sampling technique in this study uses a purposive sampling technique. Based on the established criteria, 13 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is logical regression analysis of panel data. The results showed that gender diversity, intellectual capital and inventory turnover had no effect on financial distress. Meanwhile, profitability has a significant negative effect on financial distress, and gender diversity, intellectual capital, inventory turnover and profitability together have an effect on financial distress.